KARAKTERISTIK PENJEMURAN BUJI PALA ( Myristica fragrans Houtt ) DI KABUPATEN HALMAHERA UTARA - Losir Pinoke; Handry Rawung; Ireine Longdong; Stella Kairupan (Universitas Sam Ratulangi, 2015)
Abstract This study aims to determine the drying characteristics of nutmeg which includes changes in temperature, relative humidity, drying rate against time, and the drying rate of the levels is carried out in the county air. This research was conducted in North Halmahera, Galela District. Measurements were conducted at the Laboratory of Postharvest Department of Agricultural Technology Unsrat. When the study that began in August 2013 until the end of October 2013. This research was conducted by using descriptive method, the data of the observations are arranged in the form of tabelaris, later depicted in graphic form and then discussed. Materials used in this study is the nutmeg that has been issued fulinya then spread out on a sack the size 6x8 meters, time of harvest between 6-7 months after flowering, nutmeg is blackish brown. Ambient temperature began to rise at 09:00 and decreased disore day. The highest temperature at 11:00 am with an average of 30.6 Â° C. Temperature of the material increased as well and reached its peak at 14:00 then down disore day. Similarly mat temperature peaked at 13:00 is 57.5 Â° C. Keywords: Nutmeg Seed Drying Characteristics